4 good reasons why - Butler, G. ; Bourne, F. ; Green, J. W. ; Gowridge, T. ; Whitehead, A. S. ; Abell, William H. ; Pickard, J. G.; Corah, John Reginald
1938-10 1938 1930s 12 pages October, 1938. 4 GOOD REASONS WHY — MEMBERS OF THE Saturday Hospital Society EARNING MORE THAN A £2 WEEK SHOULD HELP THE Leicester Royal Infirmary BY INCREASING THEIR CONTRIBUTION TO — PER 3d. WEEK 292/842/2/106